Is There a Difference in the Resonance Frequency Values Obtained Directly on the Implants and Abutments? - Pozzer,Leandro (Universidad de La Frontera. Facultad de Medicina, 2015)
The aim was to evaluate the differences of implant stability quotient (ISQ) between implants with external hexagon and Morse taper connectors. The study had a split mouth design, composed by 10 patients who received hybrid protocol prosthesis. In total, 40 implants (3.75 x 13 mm) were installed: on the right side, 20 external hexagon, and on the left, 20 Morse taper. After two years in function, the stability test was applied by using the MRI machine Osstell ISQ directly on the implants and on the abutments. Considering the measurements made on the implants, there were differences between HE and CM mesial (p= 0.011), lingual (p= 0.003) and distal (p= 0.006). Considering the measurements made on the abutments, there were differences between HE and CM on the buccal (p= 0.020) and lingual (p= 0.004). The trend and higher values are for the CM group. The values for Morse taper implants were always higher in a statistically significant manner, when compared to the external hexagon.